2014
DOI: 10.4102/jsava.v85i1.1094
|View full text |Cite
|
Sign up to set email alerts
|

Bovine trypanosome species prevalence and farmers’ trypanosomiasis control methods in south-western Uganda

Abstract: A cross-sectional study was conducted in Mbarara district, south-western Uganda in May 2012 to determine the burden of African animal trypanosomosis (AAT) in the semi-intensive dairy production systems where pyrethroid acaricides are frequently used in the control of tick-borne diseases (TBDs). A total of 295 cattle blood samples were taken and analysed using a single pair of primers previously designed to amplify internal transcribed spacer (ITS1) of trypanosome ribosomal deoxyribonucleic acid (rDNA). A stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…T. vivax was the least prevalent of all the species. This is contrary to other studies that have reported T. vivax as the most predominant species in the endemic parts of Uganda (5,11,14,24). However, the results are consistent with studies in Zambia (2,32,33), Nigeria (25,34), Ghana (1) and some parts of Uganda (35) where T. congolense was reported to be the most prevalent species.…”
Section: Prevalence Of Trypanosoma Spp In Goats and Cattlesupporting
confidence: 70%
See 4 more Smart Citations
“…T. vivax was the least prevalent of all the species. This is contrary to other studies that have reported T. vivax as the most predominant species in the endemic parts of Uganda (5,11,14,24). However, the results are consistent with studies in Zambia (2,32,33), Nigeria (25,34), Ghana (1) and some parts of Uganda (35) where T. congolense was reported to be the most prevalent species.…”
Section: Prevalence Of Trypanosoma Spp In Goats and Cattlesupporting
confidence: 70%
“…The higher prevalence of trypanosomes in this study could probably be explained by the close proximity of the study sites to the QENP savannah grasslands that hosts various wildlife species that are possible reservoirs of Trypanosoma spp. Wildlife has previously been reported to be important reservoir and maintenance hosts of Trypanosoma spp (5,8,31). In addition, the difference in prevalence observed in Uganda could be due to variations in different geo-ecological zones and time of year for sampling (5,14,24,30).…”
Section: Prevalence Of Trypanosoma Spp In Goats and Cattlementioning
confidence: 99%
See 3 more Smart Citations